The discovery of the lymphatic system in the 17th century. Part VII: the rise of vascular injection. Issue 5 (3rd September 2021) - Suy, Raphael; Thomis, Sarah; Fourneau, Inge
Abstract: In the second half of the seventeenth century, vascular injection was introduced in anatomy for the study of the mechanism of secretion of bodily fluids, a phenomenon into which the lymphatic system plays an important role. Injection became a routine procedure in the second half of the seventeenth century. Reinier de Graaf developed an appropriate syringe to inject liquid into minuscule tubules. He was the first to observe that water injected into seminiferous tubules was partially repelled by transudation to be absorbed by neighbouring lymph vessels. He also injected lymph vessels in and around the uterus and ovaries. His study friend Johannes Swammerdam developed a coloured hardening wax and Ruysch injected coloured hardening wax into vessels and ducts of lymph nodes and excretory glands. Ruysch introduced combined injection – corrosion procedures which resulted in delicate structures, including capillaries. He denied the presence of glandular structures in organs as described by Malpighi, and made blood vessels inclusive lymph vessels agents instead of aids to fluid secretion. His ideas resulted in the concept of the body being completely vascular, a theory which became commonplace in Dutch medical circles. Antony Nuck, the professor in medicine at the Leiden University, injected an amalgam of quicksilver and tin for further evaluation of the lymphatic system. He thought that lymph vessels originated from distal arteries and sustained that the shape of pores in these arteries determined the mechanisms of secretion in secretory glands and in lymph glands. He introduced lymphography.